Significance of nasal septum angulation and its association with rhinosinusitis symptom scores - Lazim, Norhafiza Mat; Abdullah, Abdul Mokhti; Abdullah, Baharuddin; Ismail, Zul Izhar Mohd (Pusat Pengajian Sains Perubatan, 2020)
Objective: The aim of the study was to determine the association of angulation of nasal septum with the severity of rhinosinusitis as measured by symptom score and Visual Analog Score (VAS). Method: The study was performed as a cross sectional study conducted at two different centres in Malaysia. Ninety-eight patients who were diagnosed with rhinosinusitis and fulfilled the selection criteria were assessed as for the symptom score and VAS and the measurement of angulation of nasal septum was performed through a coronal view of CT paranasal sinuses in bone window setting at osteomeatal complex level. Results: The result obtained from one-way ANOVA test revealed a significant association between category of severity of septal angulation and the symptom score of rhinosinusitis (p=0.025). In addition, the result obtained from one-way ANOVA test also revealed a significant association between category of severity of septal angulation and the VAS of rhinosinusitis (p<0.05). Conclusion: Severity of nasal septum angulation may be significantly associated with severity of rhinosinusitis based on symptom score and VAS. These findings could be used in tailored ma